Juridical Review of The Legality of Business Use Rights Designated by The Government to be Forest Areas (Study of Tanjung Balai District Court Decision No. 04/Pdt.G/2020/PN.Tjb) - Tambunan, Kiki Ayu Lestari; Yamin, Muhammad; Zaidar, Zaidar; Azwar, Tengku Keizerina Devi (Universitas Medan Area, 2024)
Forest areas are certain areas designated by the government to be maintained as permanent forests. If an area can be said to be a forest area, it must go through four stages, namely designation of the forest area, arrangement of forest area boundaries, mapping of the forest area, and determination of the forest area. Regarding forest areas, it is regulated in Law No. 41 of 1999 concerning Forestry, Law No. 11 of 2020 concerning Forestry Cluster Job Creation, and Ministerial Decree No. 579/Menhut-II/2014, dated June 24, 2014, concerning Forest Areas of North Sumatra Province. This research was carried out through a descriptive type of normative research. Source of library research data, primary data. then analyzed using qualitative analysis. The research results show that the regulations regarding forest areas in North Sumatra province issued by the Ministry of Environment and Forestry have a lot of land that overlaps with land that has land rights such as cultivation rights. As happened in Tanjung Balai District Court Decision No. 04/Pdt.G/2020/Pn.Tjb, in its considerations, the panel of judges took into account the history of the issuance of the cultivation rights because the cultivation rights